PENYELESAIAN SENGKETA MEDIASI DITINJAU DARI PERSPEKTIF PERATURAN MAHKAMAH AGUNG NOMOR 1 TAHUN 2016 - Nadila Salim; Devi Siti Hamzah Marpaung (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Dispute resolution can be carried out through a litigation process or a non- Dispute resolution can be carried out by means of a litigation process or a non-litigation process. Dispute resolution by means of the litigation process is the process of resolving disputes through the courts. Meanwhile, non-litigation settlement is a dispute resolution process carried out outside the court which often occurs with alternative dispute resolution. There are various ways of resolving non-litigation disputes, especially what will be discussed in this paper is dispute resolution through Mediation. Mediation provisions are regulated in the Republic of Indonesia Court Regulation Number 1 of 2016 Mediation Procedures in Court (Furthermore, it will be carried out with PERMA No. 1 of 2016) which is a substitute for Supreme Court Regulation Number 1 of 2008. . If not through the mediation procedure, the dispute resolution violates the provisions of Article 130 HIR and or 154 Rbg which results in the decision being null and void.